Recognition of prior learning: The CIPP model in Early Childhood Teacher Education program - Widianti, Yessi Mey; Haryono, Bambang Santoso; Anggaini, Niken Lastiti Veri (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
The early years from birth to age five are critical for children's cognitive and socio-emotional development. Supporting this development is challenging for teachers, who must not only design learning experiences but also manage meaningful learning environments for children. Effective Early Childhood Education (PAUD) requires teachers with a bachelor's degree relevant to PAUD. However, many early childhood teachers do not have this qualification, which can hinder the implementation of meaningful learning. The Recognition of Prior Learning (RPL) program offers a solution by providing a pathway for teachers to achieve a relevant degree. This research aims to provide a comprehensive description of the achievement of the Recognition of Prior Learning Program in the S-1 PG PAUD Study Program at the State University of Surabaya in terms of CIPP (Context, Input, Process, Product). This study used a descriptive qualitative approach by collecting data through observation, documentation, and semi-structured interviews. This research focuses on the evaluation of the RPL program at the S-1 PG PAUD program at the State University of Surabaya using the Context, Input, Process, Product (CIPP) model. The results showed that the RPL program contributed positively to improving the professionalism and competence of PAUD teachers, especially in Surabaya. The findings in this study provide important implications for universities as RPL program organizers and expansion of collaboration between program organizers and other local governments.